An Empirical Estimation of Underground Thermal Performance for Malaysian Climate - Mukhtar A.; Yusoff M.Z.; Ching N.K. (Institute of Physics Publishing, 2023)
Heat transfer; Meteorology; Temperature; Empirical estimations; Engineering applications; Mean annual air temperatures; Meteorological data; Soil temperature; Temperature changes; Thermal Performance; Weather stations; Soils